Full-needle geometry: application in a high-voltage corona discharge model with large-scale space. (21st June 2021) - Li, Dingchen; Li, Jiawei; Li, Chuan; Wang, Pengyu; Liu, Zhi; Ming, Zhang; Yang, Yong; Pan, Yuan; Yu, Kexun
Abstract: Corona discharge is widely used in many fields, such as drying, temperature control, propulsion, combustion-supporting, etc. In order to solve the problem of the small calculation space of the existing needle electrode discharge model, in the previous work, we proposed a hybrid method based on the combination of hydrodynamic fluid model and ion flow transport equations to study the corona discharge characteristics of the needle electrode in a large-scale space. However, as the voltage increases, the discharge source of the needle electrode changes from a single source (needle tip) to multiple sources (needle tip and needle body). The half-needle geometry used in the hydrodynamic fluid model ignores the needle body, causing the hybrid model to fail to converge under high voltage conditions. Therefore, we propose a full-needle geometry to replace the half-needle geometry in the hydrodynamic fluid model to expand the voltage range of the hybrid model. The calculation results show that the full-needle geometry can converge to the high-voltage hybrid model. The upper limit of the calculated voltage is increased from 20.9 kV to 41 kV, and the research voltage range has been increased by nearly two times. In addition, a needle-ball electrode device was adopted to verify the accuracy of the model. This research not only expands the calculation voltage range of the hybrid model, but also implies the potential of the hybrid model to be used in the multi-source discharge model.